Multichannel SPR biosensor for detection of endocrine-disrupting compounds - Dostálek, J; Pribyl, J; Homola, J; Skládal, P (Analytical and bioanalytical chemistry, 2007)
A surface plasmon resonance (SPR) biosensor for simultaneous detection of multiple organic pollutants exhibiting endocrine-disrupting activity, namely atrazine, benzo[a]pyrene, 2,4-dichlorophenoxyacetic acid (2,4-D) and 4-nonylphenol, is reported. The biosensor utilizes a multichannel SPR sensor based on wavelength modulation of SPR and wavelength division multiplexing (WDM) of sensing channels, antibodies as biorecognition element and a competitive immunoassay detection format. An analysis time of 45 min (including 30-min incubation of the sample with antibodies) and limits of detection as low as 0.05, 0.07, 0.16 and 0.26 ng mL(-1) are demonstrated for benzo[a]pyrene, atrazine, 2,4-D and 4-nonylphenol, respectively. The biosensor is also shown to be regenerable and suitable for repeated use.
Keywords: Endocrine Disruptors; Immunoassay; Surface Plasmon Resonance; kyselina 2,4-dichlorfenoxyoctová; povrchová plasmonová rezonance; fenoly; Phenols; endokrinní disruptory; Time Factors; časové faktory; Sensitivity and Specificity; 2,4-Dichlorophenoxyacetic Acid; senzitivita a specificita; Biosensing Techniques; imunoanalýza; atrazin; Atrazine; biosenzitivní techniky; benzopyren; Benzo(a)pyrene